Effect of Community Contracting on Decreasing Construction Cost - Al- Gunaid, Ahmed M. Fadhel (Thamar University Journal of Natural & Applied Sciences, 2023)
Construction Implementation based on traditional methods in remote areas may leads to high cost, tuff Topography as well as difficulty of access make the contractors avoiding works in such places, also the tiny investments of small projects in remote areas are not attractive to contractors, so the competition is very low or absent and the price accordingly is very high. Sometimes the projects cannot be implemented at all. This research discuses a new approach of implementation that can replaced the traditional one and leads to reduction of cost, it improves the use of local resources including human resources as well.